The unbearable lightness of legalism : the historical role of social morality in South East Asian international politics - Chong, Alan (2020)
The application of law in South East Asia frustrates many scholars due to its subliminal character. I call this subliminal form of law ‘legalism’. This article adopts the method of historical sociology to trace three evolutionary phases in South East Asia’s international history of legalism to illuminate the cumulative mixture of informality beneath formality in the practice of legalism via ‘social morality’. In pre-colonial times, divinely-guided moral censure and the ethical reputation of particular rulers passed for proto-intersocietal law. In colonial times, international law was foisted by Western powers onto the informal social morality of the region, resulting in power politics operating behind legal manoeuvres. The advent of ASEAN saw a reversion to a preference for even greater informality and soft law. Finally, the post-colonial era witnessed experimentation with Westphalian international law. This has resulted nowadays in a cumulative halfway house of soft legalism operated through diplomatic social morality.